FORMULATION AND EVALUATION OF PEEL-OFF MASK PREPARATION OF ETHANOL EXTRACT OF RARU BARK (COTYLELOBIUM MELANOXYLON PIERRE) - Remin Serawati Simanjorang (PHARMACON, 2026)
Background: The use of natural as active compounds in cosmetic product has increased due to growing public awareness of product safety and quality. Raru bark (cotylelobium melanoxylon perre) contains various secondary metabolites with antioxidant potential, yes its application in cosmetic formulations remains limited this study aimed to formulate and evaluate a peel-off facial mask containing ethanol extract of raru bark. Methods: this experimental study included plant determination preparation of simplicia, extraction using 80% ethanol, phytochemical screening, formulations of peel-off mask with different eextract concentrations, and physical evaluation of the formulations. The evaluations comprised organoleptic properties, homogeneity, PH, viscosity, spreadability and drying time to assess the quality of the formulations. Results: phytocmical screening revealed the presence of flavonoid, tannins, saponins,alkaloids, glycosides, and steroid/triterpenoid compound in the ethanol extract. All peel-off mask formulations exhibited good organoleptic stability and homogeneity. The pH values were the physiological range of skin, while spreadability and drying time met the required standards. Variations in extract concentration influenced the viscosity of the formulations. Conclusion: ethanol extract of raru bark can be successfully formulated into a peel-off mask that meets physical quality requirements and shows potential as a natural-based cosmetic product.